Waste management a modern approach - Bonn, Victor (New York, NY, USA Callisto Reference, 2015)
A modern approach in the field of waste management has been extensively discussed in this profound book. Solid waste management poses significant challenges for society because of its great variability in composition and production, and also due to its environmental and sanitary effects. For the purpose of fighting against this situation, this book has been compiled of analyses of technical and conceptual advancements and experiences gained through research and development projects worldwide. In addition to decreasing generation, regarded as the most preferable practice, this book also presents alternatives of valuation for potentially recoverable waste and techniques to decrease final conditioning and disposition risks. The book also covers the political, technical, social and economic aspects for the purpose of finding solutions for solid waste management.
Includes bibliographical references.
Keywords: Refuse and refuse disposal -- Research